Answer:
7
Step-by-step explanation:
Use secant-tangent product theorem.
1. Set up the equation
(x-3)(x-3+5) = (x-1)²
2. Solve
(x-3)(x+2) = (x²-2x+1)
(x²-x-6) = (x²-2x+1)
3. Solve for x
Subtract x² from both sides
-x-6 = -2x+1
Add 2x and 6 to both sides
x = 7
It would be X = 8 and since there is no slope there is no Y
Let's first turn 1 9/10 into an improper fraction, which is 19/10
so if R/12 equa;s 19/10, cross multiply
10r equals 228
divide both sides by 10, you get r= 22.8
Answer:
0
Step-by-step explanation:
1^2=1
2^2=4
3^2=9
We can stop here because the from here on forward they are bigger than 10 itself.